The Biological Role of Conoporins, Actinoporin-like Pore-Forming Toxins from Cone Snails - Matija Ruparčič; Gašper Šolinc; Simon Caserman; Juan Carlos Garcia Galindo; Manuel Jimenez Tenorio; Gregor Anderluh (Toxins)
Cone snails are a large group of marine gastropods that produce a complex mixture of toxic compounds to hunt prey and defend against predators. The majority of the venom comprises small toxic peptides named conotoxins, which target membrane receptors. In contrast, a smaller part of the venom contains larger proteins and conoproteins, which are thought to be involved in conotoxin maturation and the envenomation process, respectively. Interestingly, many species of cone snails contain conoporins, which are similar to actinoporins—pore-forming toxins found in sea anemones. These actinoporin-like proteins (ALPs) have recently been detected in many molluscan species, and only a few have been experimentally characterized. Due to being highly expressed in the venom gland of many cone snail species, conoporins are thought to play an important part in the envenomation process. Despite this, the exact function of conoporins is currently unknown. We propose several hypotheses aiming to elucidate their biological role.